2019
DOI: 10.1002/nau.24113
|View full text |Cite
|
Sign up to set email alerts
|

Are three‐day voiding diaries feasible and reliable? Results from the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) cohort

Abstract: Aims The aims of this study were to assess the completeness of voiding diaries in a research context and to correlate diary data with patient‐reported questionnaires. Methods Men and women enrolled in the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) were given a 3‐day voiding and fluid‐intake diary to fill‐out. Diaries were assessed for completeness and intake‐output imbalances. They were assigned to one of four categories based on a percentage of missing data and fluid imbalance: no dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…The majority of patients with LUTS are elders, and collecting urine in a cup and measuring the volume correctly may be difficult for some of them. It has been also reported that compliance and accuracy of the voiding diary drops significantly after a duration of 3 days 10,11 . For female patients, it requires extra effort in voiding into a cup than male patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The majority of patients with LUTS are elders, and collecting urine in a cup and measuring the volume correctly may be difficult for some of them. It has been also reported that compliance and accuracy of the voiding diary drops significantly after a duration of 3 days 10,11 . For female patients, it requires extra effort in voiding into a cup than male patients.…”
Section: Discussionmentioning
confidence: 98%
“…It has been also reported that compliance and accuracy of the voiding diary drops significantly after a duration of 3 days. 10,11 For female patients, it requires extra effort in voiding into a cup than male patients. For these patients, the bothersome hygiene issues and accuracy concerns may be significantly bigger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A voiding diary is a simple, noninvasive, and inexpensive method of collecting somewhat objective information regarding LUTS and/or catheterization habits. 4 Patients who do not appear able to provide accurate intake and voiding information from recall should be directed to complete a diary. 5 The pad test is a noninvasive, inexpensive tool used to acquire objective data in confirming the diagnosis of incontinence, assessing its severity, aiding in treatment, and may be used as a diagnostic and outcomes tool.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…Owing to the widespread use of bladder diaries in clinical practice and research, researchers are trying to design userfriendly electronic applications for recording the bladder diary, making the process easier for both patients and clinicians [7][8][9]. Considering the fact that 95.5% of adult Iranian women referred to urology clinic have at least one LUTS, the aim of the current study is to translate the ICIQ bladder diary and evaluate the validity and reliability of the Persian version of the ICIQ bladder diary, thus allowing the standardization of data collection for both clinical and research purposes.…”
Section: Introductionmentioning
confidence: 99%